Pertussis immunisation during pregnancy: Antibody levels and the impact of booster vaccine. Issue 35 (16th August 2021) - Garlasco, Jacopo; Bordino, Valerio; Marengo, Noemi; Rainero, Erika; Scacchi, Alessandro; Ditommaso, Savina; Giacomuzzi, Monica; Bert, Fabrizio; Zotti, Carla Maria
Highlights: Vaccination in pregnancy is greatly effective in ensuring high antibody coverage. There are wide differences in anti-PT IgG between vaccinated and unvaccinated women. High IgG titres are strongly encouraging with a view to transplacental immunity. Vaccinated women had protective levels of antibodies at 33–37 pregnancy weeks. Vaccinating pregnant women against pertussis is still a valuable preventive strategy. Abstract: Pertussis (whooping cough) is a highly infectious disease caused by Bordetella pertussis . Mothers lacking adequate immunity and contracting the disease represent the biggest risk of transmission to new-borns, for which the disease is often a threat. The aim of the study was to estimate the frequency of pertussis susceptibility among pregnant women, in order to point out the need for a vaccine recall during pregnancy, and to evaluate the antibody response in already vaccinated women. A cross-sectional observational study was conducted in the blood test centre of "St. Anna" Obstetrics and Gynaecology Hospital in Turin (Piedmont, Italy). Eligibility criteria included pregnant women coming to the centre for any blood test, aged 18 or above and with gestational age between 33 and 37 weeks at the moment of the blood draw. The data collection was carried out from May 2019 to January 2020 and the concentration of anti-Pertussis Toxin (anti-PT) IgG was measured through the Enzyme-Linked Immunosorbent Assay (ELISA) technique. Two-hundred women (median age 35) were enrolled: 132 (66%) had received at least one dose of pertussis vaccine, 82 of which during pregnancy. Recently vaccinated women had significantly higher antibody titres (even 12–15 times as high) compared to those vaccinated more than 5 years before or never vaccinated at all (p < 0.0001). Moreover, 95.1% of recently vaccinated women had anti-PT IgG levels above 10 IU/ml, and 85.4% above 20 IU/ml, while the same proportions were as low as 37% and 21% (respectively) in the group of women not vaccinated in pregnancy. This study confirmed that the vaccination is greatly effective in ensuring high antibody titres in the first months after the booster vaccine, with considerable differences in anti-PT IgG compared to women vaccinated earlier or never vaccinated at all, and therefore vaccinating pregnant women against pertussis still represents a valuable strategy.